Menyulap Sampah Plastik Menjadi Spot Foto Menarik: Upaya Reduksi Sampah Dan Daya Tarik Wisata - Helniana, Helniana; Muliyani, Siti; Anisa, Anisa; Ferdiansya, Ferdi; Sahar, Bahar; Ambo, Hapsa; Setiawan, Fandi; Syaiful, Muhammad; Kartomo, Kartomo (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service aims to address the issue of waste spreading in Putura Beach, Watubangga District, Kolaka Regency, and Southeast Sulawesi Province by transforming waste into something beneficial, based on the Participatory Action Research (PAR) method. Through systematic observation, we comprehend the process of processing plastic waste into creative objects. As a result, used plastic bottles have been successfully transformed into attractive photo spots with high aesthetic value. These efforts not only solve local waste problems but also create a new attraction for local tourism. Thus, the goal of sustainable community service is achieved, providing a positive impact on the environment and the local economy, as well as increasing the active participation of the community in sustainable